2009
DOI: 10.1099/mic.0.033084-0
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient-starved, non-replicating Mycobacterium tuberculosis requires respiration, ATP synthase and isocitrate lyase for maintenance of ATP homeostasis and viability

Abstract: The ability of Mycobacterium tuberculosis to persist in its human host despite extensive chemotherapy is thought to be based on subpopulations of non-replicating phenotypically drugresistant bacilli. To study the non-growing pathogen, culture models that generate quiescent organisms by either oxygen depletion in nutrient-rich medium (Wayne model) or nutrient deprivation in oxygen-rich medium (Loebel model) have been developed. In contrast to the energy metabolism of Wayne bacilli, little is known about Loebel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
274
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(293 citation statements)
references
References 36 publications
19
274
0
Order By: Relevance
“…We incubated Mtb in PBS to simulate nutrient-limited conditions. Starvation in PBS confers on Mtb a high level of phenotypic tolerance to most TB drugs, including RIF, isoniazid (INH), streptomycin (STREP), moxifloxacin (MOXI), ethambutol (ETH), and bedaquiline (TMC207) (20)(21)(22). The reported 90% Loebel-cidal concentration of Mtb nutrientstarved for 14 d was 25 μM for RIF, informing the use of high doses of rifamycins for our experiments (20).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…We incubated Mtb in PBS to simulate nutrient-limited conditions. Starvation in PBS confers on Mtb a high level of phenotypic tolerance to most TB drugs, including RIF, isoniazid (INH), streptomycin (STREP), moxifloxacin (MOXI), ethambutol (ETH), and bedaquiline (TMC207) (20)(21)(22). The reported 90% Loebel-cidal concentration of Mtb nutrientstarved for 14 d was 25 μM for RIF, informing the use of high doses of rifamycins for our experiments (20).…”
Section: Resultsmentioning
confidence: 72%
“…This was in question because DD Mtb generation proceeded most quickly when RIF was used at a concentration (100 μM) far above its minimal bactericidal concentration for replicating bacteria (0.01-0.08 μM) (20,21). The need for high concentrations of RIF may reflect impaired uptake of RIF by starved Mtb (21) or could be related to the phenotypic RIF resistance attributed to stress-induced protein mistranslation (39).…”
Section: Discussionmentioning
confidence: 99%
“…In such states metabolic activity must be maintained at a very low rate. Gengenbacher et al (2010) reported that in response to nutrient starvation Mycobacterium tuberculosis was able to downregulate its ATP levels to one fifth that of normal. As a consequence of this the bacterium entered a non-replicating state, and this enabled it to resist the effects of anti-tuberculosis drugs.…”
Section: Factors Affecting Intracellular Atp Contentmentioning
confidence: 99%
“…While glyoxylate continues fueling the glyoxylate cycle, succinate replenishes the TCA cycle (Vanni et al 1990). The relevance of isocitrate lyase, and consequently the importance of the glyoxylate cycle in surviving nutrient-depleted conditions, had been demonstrated previously (Idnurm & Howlett 2002, Gengenbacher et al 2010. The down-regulation of a central enzyme of the glyoxylate cycle thus indicates a favorable substrate supply to the TCA cycle.…”
Section: Shifts In Protein Patterns Suggest a Favorable Nutrient Statmentioning
confidence: 80%